SOME REFLECTIONS ON THE WORK OF TIMUR PULATOV (Scientific journal of the Fergana State University, 2023)
The article is devoted to the work of the talented writer Temur Pulatov. The necessity and relevance of the problem posed in the introduction are revealed. The literature section analyzes the works of Russian and Uzbek scientists, such as Olga Alimova, Elvira Abutalieva, Kazakhboy Yuldashev, Eleonara Shafranskaya, Aziza Baltabayeva, and expresses the points to which they pay attention. Thus, the methodology of work was determined. The conclusions of the analysis are listed in four paragraphs. In the analytical section on this topic, the main character of Temur Pulatov's story "Watchtowers" is partially analyzed. Then we are talking about a story called "The Girl in the Cave". At the same time, attention is drawn to the artistic image and attitude to the characters of Camilla, Esther, Ackman through the narrator's speech. Ideas are put forward about the writer's artistic perception of reality, universal values, holistic understanding and comprehension of Eastern and Western culture. At the end of the article, Temur Pulatov seeks to highlight universal human problems, the problems of modern man on the example of traditions formed during a long historical development, and his unique style of expressing the influence of a small image on the psyche of Vali Bobo, which was considered large, leading in the course of events, it is noted that it exists and thereby revealed the problem of self-consciousness. As a result of the analysis of the story, it is shown that through family issues, parental and child relationships, attention was paid to the problem of spiritual loneliness in the psyche of people.